2022
DOI: 10.3389/fimmu.2022.853009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vertical Transmission of Respiratory Viruses to the Offspring

Abstract: Overt and subclinical maternal infections in pregnancy can have multiple and significant pathological consequences for the developing fetus, leading to acute perinatal complications and/or chronic disease throughout postnatal life. In this context, the current concept of pregnancy as a state of systemic immunosuppression seems oversimplified and outdated. Undoubtedly, in pregnancy the maternal immune system undergoes complex changes to establish and maintain tolerance to the fetus while still protecting from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 111 publications
(207 reference statements)
1
35
0
Order By: Relevance
“…Immunologic, physiologic, and anatomical changes that occur during pregnancy cause suppression of the immune system, making pregnant women and their foetus more vulnerable to COVID-19 infection morbidity and mortality compared to non-pregnant women [ 7 ]. The current systematic review and meta-analysis was aimed to estimate the pooled prevalence of pregnant women KAP towards COVID-19 infection prevention and its associated factors in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunologic, physiologic, and anatomical changes that occur during pregnancy cause suppression of the immune system, making pregnant women and their foetus more vulnerable to COVID-19 infection morbidity and mortality compared to non-pregnant women [ 7 ]. The current systematic review and meta-analysis was aimed to estimate the pooled prevalence of pregnant women KAP towards COVID-19 infection prevention and its associated factors in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…As of 6 October 2021, a total of 1,637 SARS-CoV-2 infections during pregnancy and 15 deaths were reported in Mississippi [ 5 ]. Immunologic and physiologic changes occurred during pregnancy predispose women to develop severe illness from respiratory infections including SARS-CoV2 and respiratory syncytial virus influenza virus (RSV) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the few studies that uses these criteria reported positive cases relating to intrauterine transmission of SARS-CoV-2 in neonates ( 13 ). Certain respiratory virus have also been seen in vertical transmission to the offspring during pregnancy [see ref ( 14 )], though whether this is a local or systemic effect, still requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have suggested a role of immunity duration, which decreased during the time and without exposure to RSV [ 26 ]. Even pregnant women could have had reduced exposure to RSV, whose infection, especially during the third trimester of pregnancy, could protect new-borns and infants against RSV infection through transplacental transfer of antibodies, antibodies synthesized by the fetus, and antibodies contained in breast milk [ 27 , 28 , 29 ]. Lung microbiota composition may also play a role in the susceptibility to viral infections [ 30 ].…”
Section: Discussionmentioning
confidence: 99%